Time perspective, approaches to learning, and academic achievement in secondary students - Janeiro, Isabel Nunes (2019)
Previous research suggests that both the presence of an extended future time perspective and the generic use of a deep approach to learning predict academic achievement and overall adjustment to school. The present study aimed to investigate how the different dimensions of time perspective (future, present, past, and negative future) influence secondary students' approaches to learning and academic achievement. Participants were 400 students attending the 11th grade (248 girls and ﻿152 boys; Mean = 16.70, SD = 0.94) at six Portuguese public schools. Structural equation modeling analysis showed that future time orientation influenced academic achievement via deep and achieving approaches to learning, while past orientation and negative future influenced achievement via surface approaches to learning. Present orientation was not related to approaches to learning but had a small direct negative effect on academic achievement. Implications are discussed, along with limitations and suggestions for future research.